MUSIC COMPOSITION "THE SOUTHERN ZONE" FOR THE PERFORMANCE AT SAMILA JAZZ FESTIVAL 2022 - Kheawprang, Anuwat (Fine Arts Journal: Srinakharinwirot University, 2024)
The “Southern Zone” is a song performed at the Samila Jazz Festival 2022, an annual music festival organized by the Songkhla Provincial Administrative Organization (PAO Songkhla) in collaboration with the Western Music Department of the Faculty of Fine Arts, Songkhla Rajabhat University. The event took place on July 29-30, 2022, at the new public park in Songkhla Province. The primary objectives of the festival were to foster a network of jazz music enthusiasts and to promote tourism in Songkhla Province. This composition was crafted with the concept of blending various musical elements and styles. The melody incorporates the essence of Southern Thai folk music within the framework of a 12-bar blues structure. The harmonic progression features numerous jazz techniques, such as tension chords, chromatic chords, and the ii – V progression. Additionally, the arrangement designates improvisational sections for musicians, specifically the saxophone, guitar, and keyboard, each performing two choruses within the 12-bar blues structure. The performance also includes improvisations by the bass and drum set in the form of trading solos.